2014
DOI: 10.4103/1119-3077.130228
|View full text |Cite
|
Sign up to set email alerts
|

Falls among pregnant women in Enugu, Southeast Nigeria

Abstract: Falls during pregnancy is common in Enugu, Nigeria. It is, therefore, recommended that women should be counseled during pregnancy on this public health problem and the above-identified risk factors emphasized in order to reduce the prevalence and morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 2 publications
1
20
1
Order By: Relevance
“…Our study revealed that women 30 years and above were significantly more likely to fall during pregnancy, controverting studies that found higher incidence of falls in younger women because they are more active [1, 21]. The observed variance could be due to geographical/racial differences, sample sizes of the studies, and cultural diversity of the population studied.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Our study revealed that women 30 years and above were significantly more likely to fall during pregnancy, controverting studies that found higher incidence of falls in younger women because they are more active [1, 21]. The observed variance could be due to geographical/racial differences, sample sizes of the studies, and cultural diversity of the population studied.…”
Section: Discussioncontrasting
confidence: 75%
“…Significantly, multiparous women were more likely to fall during pregnancy from our survey. Although another study from southeast Nigeria concluded otherwise [21], the sample size was much smaller. Multiparous women were more likely to be involved in domestic duties as they care for their large families.…”
Section: Discussionmentioning
confidence: 99%
“…Endometriosis is a common, although mysterious and fascinating, gynecological condition with diverse clinical manifestations and high variability. It has an unpredictable clinical course and results in diminished quality of life (Okeke et al, 2011). Despite extensive research, the pathogenesis of endometriosis remains unclear because it is complex.…”
Section: Discussionmentioning
confidence: 99%
“…The fall rate identified from this survey was 26%. This is inkeeping with the figures quoted by studies from south-eastern Nigeria (32.5%) [17], and other parts of the world [1,6,18]. Thus, it is clear that accidental maternal falls are issues of public health importance in Nigeria.…”
Section: Discussionmentioning
confidence: 76%